Qira’at ul Imam ‘Abdullah Ibn ‘Abbas (R.A) and their Impact on the Interpretation of the Qur’an - Ahmad Ali (Journal of Islamic and Religious Studies, 2018)
Ṣaḥabah (R.T.A) especially Ahal-Bait have distinct position among Muslim Ummah. They have served Islamic religion in its initial period and preserved it for the generations to come. Haḍrat ‘Abdullah Ibn e ‘Abbas (RTA) was not only a Ṣaḥabi-e–Rasool (companion of the Prophet), but he was also a member of the family of Muḥammad (peace be on him). He remained in his company during his journeys and his stays in different places and got (training) from him. Muḥammad (peace be on him) made a special prayer for him i.e. “O Allah, give him understanding in religion and teach him the interpretation of the Qur’ān.” In this article the researcher aims to analyse and explain his services in the field of Islamic Sciences, Tafsir ul,Qur’ān specially the number and detail of Qiraat e Mutawatirah and Shaẓah narrated by him and their effects on the Science of Tafsir ul .Qur’ān.